(3GdSLd Gdefgi ajg Yf GdNeQs ((3GdCejQ YjSi GdJfhNi s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg GdPi CYR GdZSdGe HChdjGAg GdeJbjf hcJH gPG GdefThQ djbQC Ydi GdNGU hGdYGe ef GdChdjGA hGdQYjI HGdfgi Yf GdJYQV dTQH TF ef GdeScQ Ydi ENJdGa CUfGag s
(3BNQgG (B:s
(3hef TedJg OYhI GdMb ef cGaI GdfGS CLeYjf hGdMeO ddg hMOg hUdhGJg Ydi QShdg NGJe GdfHjjf hSdGeg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds